Analysis of Government Budgeting for Health: Case Study of COVID-19 in East Java Province, Indonesia - Rokhmah, Dewi; Ridzkyanto, Ricko Pratama; Khoiron, Khoiron (Kesmas, 2020)
The COVID-19 in Indonesia was first reported in March 2, 2020 with two cases, and the number has increased each day until April 23, 2020 and reached 7,775 positive cases of COVID-19. East Java Province ranks the third in Indonesia with 662 cases. COVID-19 requires a health financing system aimed for COVID-19 patients and hospital services. The study aimed to describe the amount of COVID-19 and the use of funds for COVID-19 in East Java Province. This study applied descriptive analytic method. Secondary data analysis used the COVID-19 fund data of 31 districts/cities in East Java Province from the Regional Development Agency of East Java Province in period of March 23 - April 23, 2020. The results showed that the total budget for COVID-19 in the province was worth IDR 2,102,600,000,000 divided for Curative IDR 727,654,880,535, Promotive Preventive IDR 97,134,092,873, Social Safety Net IDR 877,301,513,766 and Recovery IDR 400,50,512,826. The total fund for COVID-19 per capita in the province was IDR1,997,139 divided for Curative IDR 691,158, Promotive Preventive IDR 92,262, Social Safety Net IDR 833,299 and Recovery IDR 380,421. According to districts, the highest budgeting is Jember District, Surabaya City, and Gresik District. The highest per-capita funds, according to districts/cities, are Batu City, Jember District, and Trenggalek District.